The implementation and evaluation of HIV symptom management guidelines: A preliminary study in China - Zheng Zhu; Yan Hu; Hui-wen Li; Mei-juan Bao; Lin Zhang; Li-jun Zha; Xue-hong Hou; Hong-zhou Lu (Elsevier, 2018)
Objective: The overarching objective of this study was to examine the effectiveness of HIV symptom management guidelines in China in reducing the incidence and severity of symptoms and improving patients' quality of life. Methods: We conducted a controlled, pre- and post-implementation design in the HIV/AIDS inpatient unit in Shanghai. Patients recruited from November 2014 to February 2015 were in the intervention group and those from October 2013 to February 2014 were in the control group. There were 74 patients in each group. Participants in the intervention group received interventions based on the HIV symptom management guidelines. Overall symptom severity, depression, and quality of life were measured in two groups at baseline, week 4, and week 8. Results: Totally 126 patients completed the research, 65 in the intervention group and 61 in the control group. The total symptom severity scores showed a statistically significant difference between groups across time (P < 0.05). It showed that frequencies of fatigue (36.9% vs. 44.3%), fever (6.2% vs. 11.5%), loss in weight (9.2% vs. 16.4%), mouth ulcers (12.3% vs. 16.4%), headaches (9.2% vs. 19.7%) and depression (F = 1.09, P > 0.05) in the intervention group were lower than those in the control group in week 8 without statistical significance. The multilevel growth mixture model indicated a greater increase in the total score of quality of life for the group treated according to the symptom management guidelines (P = 0.04). Conclusion: The evidence-based HIV symptom management guidelines can improve a patient's quality of life and relieve negative symptoms. The guidelines can be applied in a similar context to other HIV/AIDS units or clinics. Keywords: Acquired immunodeficiency syndrome, Evidence-based nursing, Evidence-based practice, HIV, Symptom management